EPIDEMIOLOGICAL FEATURES AND MEDICAL CONSEQUENCES OF ECTOPIC PREGNANCY IN KEMEROVO REGION - FETISCHEVA, LARISA E.; MOZES, VADIM G.; ZAKHAROV, IGOR S.; VOLKOV, REM V. (Fundamental and Clinical Medicine, 2018)
Aim. To determine epidemiological features and medical consequences of ectopic pregnancy in Kemerovo Region. Materials and Methods. Having collected the relevant data from the statistical records in Kemerovo Region, we analyzed incidence of ectopic pregnancy in 2010-2017 and incidence of ectopic pregnancy-related emergency surgery in 2007-2014 with the subsequent statistical analysis. Results. There was no clear trend to either growth or decline of ectopic pregnancy incidence in Kemerovo Region. The lowest incidence rate was registered in 2015 (32.3 per 1,000 completed pregnancies) while the highest rate was registered in majority of the patients received surgical treatment within the 24 hours after initial diagnosis, yet the proportion of patients who underwent surgery > 24 hours after the diagnosis significantly increased over the study period (13.1% in 2006 and 24.4% in 2017, p = 0.001). Conclusions. Despite the incidence of ectopic pregnancy did not change, the proportion of patients with non-emergency surgery increased twofold. This can be applied in evaluating the efficacy of the Federal Protocol for the Treatment of Ectopic Pregnancy.